ESTIMATION OF VARIANCES , GENOTYPIC AND PHENOTYPIC CORRELATIONS FOR SOME TRAITS OF MAIZE UNDER HIGHEST UNDUR NITROGEN ABUNDANCE - bunder, S. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The objective of this study was estimation of variances, broad sense heritability genotypic and phenotypic correlation for some traits of maize under nitrogen abundance . the experiment was conducted at the farm of the Dept. of Field Crop Sci., College of Agric., Univ. of Baghdad during the Spring and fall seasons of 2012 under level 400 Kg N. ha rate-1 . Diallel cross was performed among four maize inbred lines (Zm7, Zm607, Oh40, Zr8) to produce six single crosses in spring season . The seeds of parents and crosses were sown in fall season using R.C.B.D. with three replicates. The results showed significant difference among genotypes and the values of the genotypic variance were more than environment variance in all studied characters. The values of phenotypic coefficients of variation larger than the genotypic and the higher rate of genotypic coefficient of variation for 300 grain weight 16.74, no. of grain per row 15.05 and leaves area 12.18. furthermore high estimates of broad sense heritability were observed for all characters and the highest value 81.45 for 300 weight grain and 75.31 for leaves area .The grain yield gave high significant negative genotypic and phenotypic with silking date and positive with plant height , leaves area , no. of grain per row , 300 grain weight. It was concluded that a breeder can use leaves area , no. of grain per row and grain weight as selection index in selection program of maize under high nitrogen